2005
DOI: 10.1007/s10517-005-0475-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cu2+ in Free Radical Oxidation of Human Serum Albumin and L-Tyrosine Dipeptide with Multicomponent Metal-Containing Xenobiotic

Abstract: Cu(2+) entering the composition of multicomponent metal-containing xenobiotic in vitro initiated free radical oxidation of human serum albumin and L-tyrosine dipeptide. Oxidative modification was accompanied by the formation of derivatives of amino acids tyrosine and tryptophan and structural changes in human serum albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The results of synchronous fluorescence spectroscopy were consistent with the results from fluorescence emission spectroscopy studies. Destruction of HSA was accompanied by the fluorescence decrease of tryptophan and tyrosine residues . However, the maximum peaks of tryptophan and tyrosine residues of HSA shifted scarcely, which showed that the microenvironment of tryptophan and tyrosine residues of HSA kept unchanged .…”
Section: Resultsmentioning
confidence: 93%
“…The results of synchronous fluorescence spectroscopy were consistent with the results from fluorescence emission spectroscopy studies. Destruction of HSA was accompanied by the fluorescence decrease of tryptophan and tyrosine residues . However, the maximum peaks of tryptophan and tyrosine residues of HSA shifted scarcely, which showed that the microenvironment of tryptophan and tyrosine residues of HSA kept unchanged .…”
Section: Resultsmentioning
confidence: 93%
“…Cations specifically cleave peptide bonds of human IgG1 hinge region [14], play a key role in protein oxidation in vitro and in vivo causing fragmentation and modification of amino acid residues [5], enhance DNA cleavage [1], and catalyze autooxidation of biomacromolecules in the cytoplasm being present even in very low concentrations [3]. Therefore absorption of Cu 2+ ions by cells is paralleled by their obligatory reduction to less toxic Cu + [3], while the intracellular content of free copper is maintained at the level of 10 -18 M (less than one cation per cell) [3].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, copper cations modifying proteins promote the formation of intra-and intermolecular bityrosine cross-links [5], cause aggregate formation [6,7,9], stabilize the appearing supra- molecular complexes under certain conditions [1], and, as components of ceruloplasmin, provide antioxidant defense [4].…”
Section: Resultsmentioning
confidence: 99%